The Relevance of Artificial Intelligence in Teaching English in Technical Universities - Karimova , Diyora (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The rapid development of digital technologies and the growing influence of artificial intelligence (Al) are transforming modern education. In technical universities, where students are primarily focused on engineering and technological disciplines, the study of English as a foreign language plays a crucial role in professional communication and global collaboration. However, traditional teaching methods often fail to fully meet the needs of modern technical students. This paper examines the relevance and pedagogical potential of artificial intelligence in teaching English in technical universities. The study analyzes how Al-based tools can enhance language acquisition, personalize learning experiences, and increase student motivation. The integration of Al technologies such as intelligent tutoring systems, automated feedback platforms, and natural language processing tools creates new opportunities for improving the effectiveness of English language instruction.